Tracking, erosion and thermal distribution of micro‐AlN + nano‐SiO2 co‐filled silicone rubber for high‐voltage outdoor insulation. Issue 4 (1st December 2018) - Nazir, Muhammad Tariq; Phung, Bao Toan; Yu, Shihu; Zhang, Yuanyuan; Li, Shengtao
Abstract : Thermal depolymerisation induced tracking and erosion of polymeric insulators is one of the key insulation failure modes and this process adversely affects the reliability of power delivery networks. This study reports the tracking, erosion and thermal distribution of micron‐AlN and micron‐AlN + nano‐SiO2 co‐filled silicone rubber composites. A tracking‐erosion model is presented to explain how the co‐filled set of particles directly affects such mechanisms. Aluminium nitride (AlN: 5–10 μm) and silica (SiO2 : 20 nm) particles were procured for fabricating test samples. The inclined plane test according to IEC 60587 was carried out using tracking voltage method 2 with an initial applied voltage of 3 kV and a ramping rate of 0.25 kV/h over the duration of 240 min. Measurement results show co‐filled composites exhibit significantly lower physical tracking and erosion as compared to micron‐AlN filled composites. Thermal accumulation and average leakage current in co‐filled composites are found noticeably lower than micron‐filled counterparts. Moreover, the increased surface area of the combined co‐filled particles in the composites provides better scattering and reduce secondary electron collision. This may impede the release of high energy causing thermal degradation.